Stagnancy of Land Use Arrangement Former Cultivation Rights - Dwi Gatra; Syamsuddin Pasamai; Hasan Kadir; Andika Prawira Buana; Aan Aswari (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2018)
Land issues still cause problems especially in terms of usage rights that are discharged, the allocation is still limited to the obsolete concept that is still applied today, while the increasingly complex needs for the development of the suitability and more appropriate. This study formulates the extent to which the city of Makassar in reorganizing this concession as its purpose-built sustainably and sustainable future. This study uses empirical juridical and legal research supported by the results of observation. The results of this study describe the efforts undertaken by the government in this case BPN Makassar City seem less innovative so that the impact on potential obstacles of regional development and running haltingly.